Resistensi Perempuan dalam Film Series “Ash-Shafaqah” Karya Nadia Ahmad: Kajian Feminisme Kekuasaan Naomi Wolf: Feminisme Kekuasaan Naomi Wolf - Adnan, Zuhra Latifa (An-Nas, 2023)
Abstract: “This study aims to describe and uncover forms of women's resistance in ash-Shafaqah, focusing on Naomi Wolf's perspective of power feminism. The object that is the source of data in this study is a film series from Kuwait with the title Ash-Shafaqah which will be released in February 2023. The method used in this study is qualitative descriptive. Research data in the form of words, phrases, sentences, and discourses that contain elements of women's resistance. With the analysis of the power feminism approach as a framework for thinking, the results of this study show that in the film there are several forms of resistance carried out by the main female character, namely; 1) Women who have a firm disposition and confidently make their own decisions. 2) The woman in the film boldly determines and chooses her own path in life if she thinks it is right without relying on men's opinions. 3) Women with their potential are able to face various challenges, to match their position with men. 4) Women are visionaries and their experience is valuable. 5) Women have the same rights as men in obtaining justice and power.” Keywords: Feminism, Resistance, Film, Power